2016
DOI: 10.1016/j.addbeh.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk for severe outcomes and drinking status among drug users with HIV and Hepatitis C Virus (HCV)

Abstract: Objective-Among drug users with HIV and Hepatitis C Virus (HCV) infections, heavy drinking can pose significant risks to health. Yet many drug users with HIV and HCV drink heavily. Clarifying the relationship of drug-using patients' understanding of their illnesses to their drinking behavior could facilitate more effective intervention with these high-risk groups.Method-Among samples of drug users infected with HIV (n=476; 70% male) and HCV (n=1145; 81% male) recruited from drug treatment clinics, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…(36) As such, strategies must be developed that combine DAA therapy with the management of alcohol use disorder, especially as some studies have suggested that patients with an alcohol use disorder and HCV are more likely to participate in risky drinking behaviors because to them severe liver-related outcomes appear to be inevitable. (37,38) Another factor associated with the development of DCC or HCC among those with HCV and an SUD was the presence of CKD in which one was over two times more likely to be diagnosed. This finding is most likely due to the known association of renal failure in patients with advanced liver disease and HCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(36) As such, strategies must be developed that combine DAA therapy with the management of alcohol use disorder, especially as some studies have suggested that patients with an alcohol use disorder and HCV are more likely to participate in risky drinking behaviors because to them severe liver-related outcomes appear to be inevitable. (37,38) Another factor associated with the development of DCC or HCC among those with HCV and an SUD was the presence of CKD in which one was over two times more likely to be diagnosed. This finding is most likely due to the known association of renal failure in patients with advanced liver disease and HCV.…”
Section: Discussionmentioning
confidence: 99%
“…( 36 ) As such, strategies must be developed that combine DAA therapy with the management of alcohol use disorder, especially as some studies have suggested that patients with an alcohol use disorder and HCV are more likely to participate in risky drinking behaviors because to them severe liver‐related outcomes appear to be inevitable. ( 37,38 )…”
Section: Discussionmentioning
confidence: 99%